Ekstraksi dan Identifikasi Oligosakarida Ekstrak Tepung Rebung Bambu Tabah (Gigantochloa nigrociliata Buse-Kurz) Sebagai Sumber Prebiotik - Dylla Hanggaeni Dyah Puspaningrum; Ni Luh Utari Sumadewi (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2017)
Potentials of tabah bamboo shoots flour as source of prebiotics need to be explore by extracting and identifying its oligosaccharide contents, will provide complete information about bamboo tabah flour potentials. In processing tabah bamboo shoots obtained every 1000 grams of tabah bamboo shoots will be obtained ± 250 grams tabah bamboo shoots (edible part) dan will produce ± 10.08 grams of tabah bamboo shoot flour. Tabah bamboo shoots flour rendemen was ± 0.97%The extraction with 70% ethanol solvent has the highest yield (2.62%), followed by distilled water (1.28%), and ethyl acetate (0.92%).Observations made on the color and yield showed a difference, whereas the consistency of the extract did not difference.Extraction was conducted using 70% ethanol solvent, (polar), ethyl acetate (semi-polar), and distilled water. Qualitatively phytochemical analysis was conducted. The isolation of oligosaccharide was conducted using column chromatography, Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography (HPLC). The phytochemical analysis of tabah bamboo shoots flour in 70% ethanol discovers that it contains steroid, tannin, and saponin, which are antibacterial compounds. The purification of the extract of tabah bamboo shoots flour yields two main oligosaccharide components: glucose, sucrose and raffinose.